A Complete and the Most Liberal Semantics for Converging OR Gateways in Sound Processes - Prinz, Thomas; Amme, Wolfram (Complex Systems Informatics and Modeling Quarterly, 2015)
Although the semantics of converging OR gateways (also known as OR-joins) in business processes is far from trivial, they are frequently used. In this paper, we describe a general definition for soundness of processes guaranteeing the absence of deadlocks and no lack of synchronization for each possible OR-join semantics. Then, we derive a criterion — completeness — to evaluate existing approaches of OR-join semantics. As a result, no currently existing OR-join semantics is complete; therefore, there are actually correct processes being not successfully executable. For that, we provide our own approach based on a traditional relation of compiler construction; and we show that this approach is complete and can be called the most liberal possible.